Food economics : industry and markets - Hansen, Henning Otte, 1959- (London : Routledge, 2013)
'Food and food markets still enjoy a pivotal role in the world economy and the international food industry is moving towards greater consolidation and globalization, with increased vertical integration and changes to market structure. Companies grow bigger in order to obtain economies of scale and issues and such as food security, quality, obesity and health are ever important factors.This textbook analyzes the structure of the world's food economy, with particularly strong coverage on the root causes of periodic food crises and the impact of WTO measures and other agricultural policies. Bio-energy, cooperatives, regional trading blocs and liberalization are all placed under the microscope.The result is an internationally focused account of the role of food markets today with history and future trends and prospects analyzed alongside contemporary issues'--
'Food and food markets still enjoy a pivotal role in the world economy and the international food industry is moving towards greater consolidation and globalization, with increased vertical integration and changes to market structure. Companies grow bigger in order to obtain economies of scale and issues and such as food security, quality, obesity and health are ever important factors. This book describes the link between food markets and food companies from a theoretical and a business economics perspective. The relationships, trends and impacts on the international food market are presented, and the topic is related to actual business conditions. Each chapter is accompanied by questions and assignments designed to help students in their learning'--
Includes bibliographical references (p. [389]-403) and index.
Keywords: Food industry and trade; Produce trade; Food supply -- Political aspects; Globalization -- Economic aspects